Manganese residue roadbed water stabilizing layer material based on modified roasted electrolytic manganese, method and application
By modifying the combination of electrolytic manganese manganese slag and other materials after calcination, an efficient and low-cost water-stabilized layer material is formed, which solves the problems of high cost of electrolytic manganese slag treatment and low absorption, and achieves the safety of manganese slag. Efficient resource utilization.
Patent Information
- Application Number
- CN202411519440.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrolytic manganese slag treatment methods have large water consumption, high cost and small consumption, resulting in large storage capacity of electrolytic manganese slag, making it difficult to achieve large-scale harmless treatment or resource utilization.
Modified calcined electrolytic manganese slag is used as the main component of the roadbed water stabilization layer material. By combining it with cement, crude aggregate, curing agent, stabilizer and exciter, water stabilization with high curing rate and good mechanical properties are formed. Layer material.
It realizes low-cost, safe and efficient resource utilization of manganese slag, reduces treatment costs, and has good anti-seepage effect and mechanical properties of the materials, which are suitable for road construction.
Smart Images

Figure CN119409458A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource utilization of industrial waste residues, and in particular to a roadbed water-stabilizing layer material, method and application based on modified roasted electrolytic manganese slag. Background Art
[0002] Manganese is an important foundation and strategic material for my country's national economy. It is widely used in high-tech fields such as steel and non-ferrous metal smelting, electronic batteries, aerospace, and national defense industry, and plays an important role. my country is the world's largest producer, consumer, and exporter of electrolytic manganese.
[0003] Electrolytic manganese slag is an acidic waste residue produced during the production of electrolytic manganese metal by electrolysis. Its main components are SiO2, Al2O3 and CaSO4·2H2O. It has the characteristics of high water content, high viscosity and low activity. Electrolytic manganese slag belongs to Class II general industrial solid waste. The existing electrolytic manganese slag treatment and disposal technologies mainly include water washing, leaching, electrochemical method, solidification method and valuable metal recovery, but these technologies generally have the disadvantages of large water consumption, high cost and small absorption capacity, making it difficult to truly achieve large-scale harmless treatment or resource utilization.
[0004] After searching, the patent application with application number CN200910085791.1 provides a method for preparing building materials using electrolytic manganese slag, which uses raw manganese slag mixed with lime, gypsum and kaolin, and then adds water to fully stir, and then adds cement, sand and stone coarse aggregate, and sand and stone fine aggregate to form a mixture, which is vibrated and pressed by a press. The application document with application number CN201510598886.9 discloses a preparation method for active mixed materials using electrolytic manganese slag, which is prepared by adding a certain proportion of activator and reductant to the electrolytic manganese slag, and reacting the activator with the activator at high temperature for physical and chemical reaction, and the calcined clinker is cooled to obtain the active mixed material. The patent application with application number CN201910100998.5 discloses a method for preparing unburned concrete from electrolytic manganese slag, wherein coal powder and biomass straw are added to the electrolytic manganese slag, and then a mixture of water, lime and sodium silicate is added after roasting, and the mixture is excited at a temperature of 25-50°C for 1-72 hours, filtered, and the filter residue is taken, and then cement, steel slag and glycerin are added, stirred and mixed, and finally water and sand and gravel are added again for stirring and maintenance to form unburned concrete. The patent with application number CN201910860624.3 discloses a road anti-cracking water-stabilizing layer material containing electrolytic manganese slag and a preparation method thereof, which is made of electrolytic manganese slag, red mud, and composite phase change material, wherein the phase change material and expanded graphite are composited and coated with organic resin, and the heavy metals are further consolidated by stirring the electrolytic manganese slag with red mud, and the ammonia is recovered by suction filtration again, and the treated electrolytic manganese slag is dried and pulverized to form a water-stabilizing layer material. The patent application with application number CN202210163706.4 discloses a low-carbon roadbed material of electrolytic manganese slag and a preparation method thereof. The original slag sample of electrolytic manganese slag is crushed, pretreated with a deamination agent and turned over, and then 4% to 10% of mineral powder and 15% to 35% of roadbed aggregate are added for paving, rolling and curing to form a carbon-type roadbed material.
[0005] However, the above methods may cause serious pollution to the surrounding environment of production or generate a large amount of polluted wastewater, the production conditions are difficult to meet environmental protection requirements and the production cost is high; or the main component ratio of the produced cementitious material is low and the impurities are relatively high; or it is not easy to mix, and the produced concrete will show segregation or uneven aggregates; or in the process of treating the electrolytic manganese manganese slag, more difficult to treat red mud containing a large amount of strongly alkaline chemicals and trace radioactivity is introduced, which makes the treatment difficult and the effect is not good enough; or there are shortcomings such as the complexity of the process flow is too complicated and the harsh production conditions lead to great difficulties in the transformation and application of the results.
[0006] Therefore, developing a safe, efficient and low-cost technology for harmless treatment and resource utilization of manganese slag is of great significance to the development of the electrolytic manganese industry and pollution prevention and control. Summary of the invention
[0007] The purpose of the present invention is to provide a material, method and application of a water-stabilizing layer of a roadbed based on modified roasted electrolytic manganese manganese slag, which at least solves the technical problems that the existing electrolytic manganese manganese slag treatment methods generally have large water consumption, high cost and small absorption capacity, resulting in large stacking and inventory of electrolytic manganese manganese slag, difficulty in truly realizing large-scale harmless treatment or resource utilization, and high treatment cost.
[0008] According to a first aspect of the present invention, there is provided a roadbed water-stabilizing layer material based on modified calcined electrolytic manganese manganese slag, comprising raw materials mixed in the following mass proportions: 3.0%-4.5% cement, 40%-60% coarse aggregate, 14%-27% calcined electrolytic manganese manganese slag, 1.12%-2.7% curing agent, 0.4%-0.75% stabilizer, 0.4%-0.75% activator and 1.93%-3.73% water.
[0009] According to the aspects and any possible implementations described above, an implementation is further provided, wherein the cement comprises an ordinary Portland cement solution, and the components of the ordinary Portland cement solution comprise calcium silicate, calcium aluminate, calcium aluminoferrite, calcium sulfate and alkali.
[0010] According to the aspects described above and any possible implementation method, an implementation method is further provided, wherein the fine aggregate includes roasted electrolytic manganese manganese slag, and the roasted electrolytic manganese manganese slag includes raw materials in the following mass proportions: 31.80% silicon dioxide, 9.26% aluminum oxide, 5.54% iron oxide, 18.02% calcium oxide, 1.12% magnesium oxide, and 13.49% manganese oxide.
[0011] According to the aspects described above and any possible implementation, an implementation is further provided, wherein the curing agent includes quicklime; the quicklime is mixed with the calcined electrolytic manganese manganese slag to form a solidified precipitate; and the mass ratio of the quicklime to the calcined electrolytic manganese manganese slag is 8% to 10%.
[0012] According to the aspects and any possible implementations described above, an implementation is further provided, wherein the stabilizer includes calcium-based bentonite; the calcium-based bentonite adsorbs heavy metals in the roasted electrolytic manganese slag through the montmorillonite structure to prepare a cement stabilization layer.
[0013] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the activator comprises instant sodium silicate or water glass, wherein the concentration of the water glass solution is 40° Bé;
[0014] The instant sodium silicate or water glass is mixed with the cement and the calcined electrolytic manganese slag respectively, the cement is hardened and the electrolytic manganese slag network structure is prepared.
[0015] According to the above aspects and any possible implementation, there is further provided an implementation, characterized in that the coarse aggregate comprises a graded crushed stone layer;
[0016] The first-level road particle sizes of the graded crushed stone layer include: the mass ratio of the particle size of 4.75mm-9.5m is 10%, the mass ratio of the particle size of 9.5mm-19m is 35%, and the mass ratio of the particle size of 19mm-26.5m is 15%.
[0017] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the cement is ordinary Portland cement, the coarse aggregate is graded crushed stone, the curing agent is quicklime, the stabilizer is calcium-based bentonite, and the activator is quick-dissolving sodium silicate or water glass;
[0018] The mass ratios of ordinary Portland cement, graded crushed stone, roasted electrolytic manganese slag, quicklime, calcium-based bentonite, instant sodium silicate or water glass, and water are 4%, 50%, 25%, 2%, 0.5%, 0.5%, and 3.45%, respectively.
[0019] According to a second aspect of the present invention, there is provided a method for preparing a roadbed water-stabilizing layer material based on modified calcined electrolytic manganese slag, comprising the following steps: mixing a curing agent and calcined electrolytic manganese slag in a mass ratio of 8% to obtain a mixture;
[0020] Use instant sodium silicate or directly use 40°Bé water glass solution as the activator;
[0021] 0.5% by mass of an activator, 0.5% by mass of a stabilizer, 4.0% by mass of cement, and 50% by mass of coarse aggregate are added to a 27% by mass mixture, and then 3.45% by mass of water is added and mixed to obtain the roadbed water-stabilizing layer material.
[0022] According to the third aspect of the present invention, there is provided an application of a roadbed water-stabilizing layer material based on modified calcined electrolytic manganese slag, wherein the roadbed water-stabilizing layer material is evenly laid on the road, wherein the loose laying thickness is 20-25 cm, the compacted thickness is 15-20 cm, and a 22t vibrating steel wheel roller roller is used for rolling.
[0023] Compared with the prior art, the present invention has achieved the following technical effects:
[0024] (1) The present invention adopts roasting electrolytic manganese slag, which has been desulfurized and fixed with ammonia during the roasting process, and the main production line has adopted cadmium removal treatment. Therefore, during use, only the Mn in the roasting electrolytic manganese slag needs to be considered. 2+ Ions, water-soluble salts, and pH issues.
[0025] (2) The present invention utilizes roasted electrolytic manganese slag to replace part of the cement addition amount and completely replace the fine aggregate component of the traditional water-stabilized layer, and uses quicklime as a curing agent, calcium-based bentonite as a stabilizer, and quick-soluble sodium silicate or water glass as an activator to accelerate its gelation speed and curing efficiency. The implementation method of the present invention can be realized by simply modifying and adding a hopper to the mixing station. The present invention is low in cost and convenient in construction. It has been verified by indoor tests and field tests, and the results are reliable. It can solve the problem of electrolytic manganese waste slag treatment for manganese mining enterprises and the electrolytic manganese industry.
[0026] (3) The material of the present invention can be used for the construction of primary, secondary, tertiary and quaternary roads, and can also be used for the recycling of manganese slag from roasting electrolytic manganese, and the paved roads are not affected by the initial pH and are applicable to various pH ranges;
[0027] (4) The material of the present invention can completely replace the stone material of the roadbed water-stabilizing layer for filling, and has good mechanical properties and stability, especially good anti-seepage effect. It can be used within a range of 100 km. The materials are all common industrial materials or building materials, which are easy to obtain, cheap, and highly operational. Moreover, by developing and controlling the compounding ratio, it will not cause new pollution to groundwater and surface water.
[0028] (5) The present invention is to mix ordinary silicate cement, graded crushed stone, roasted electrolytic manganese slag, quicklime, calcium-based bentonite, instant sodium silicate or water glass, and water, and then mix them with the on-site mixing station equipment to start paving. The loose paving thickness is 20-25cm, the compacted thickness is 15-20cm, and a 22t steel wheel drum roller is used for 4 times of vibration rolling. The present invention can be used to 2+ The ion concentration dropped from 148 mg / L to 2.28 mg / L, and the curing rate was 98.50%, which was much better than other methods.
[0029] It should be understood that the contents described in the summary of the invention are not intended to limit the key or important features of the embodiments of the present invention, nor are they intended to limit the scope of the present invention. Other features of the present invention will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and other features, advantages and aspects of the embodiments of the present invention will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. The accompanying drawings are provided for a better understanding of the present invention and do not constitute a limitation of the present invention. In the accompanying drawings, the same or similar reference numerals represent the same or similar elements, wherein:
[0031] Figure 1 A schematic diagram of roasting electrolytic manganese slag particles based on modified roasted electrolytic manganese slag water-stabilizing layer material according to an embodiment of the present invention is shown;
[0032] Figure 2A schematic diagram of a layered structure with high specific surface area and pore volume based on bentonite, a water-stabilizing layer material of a roadbed made of modified and calcined electrolytic manganese slag according to an embodiment of the present invention is shown;
[0033] Figure 3 The present invention shows the statistical sample preparation of the spherical gelation time of the electrolytic manganese slag after modified roasting and grinding of the electrolytic manganese slag for roadbed water-stabilizing layer material according to the embodiment of the present invention;
[0034] Figure 4 A schematic diagram showing the statistical results of the gelling time of the ground powder of the electrolytic manganese slag roadbed water-stabilizing layer material after modified roasting according to an embodiment of the present invention is shown;
[0035] Figure 5 A schematic diagram of a sample for testing the unconfined compressive strength of a roadbed water-stabilizing layer material based on modified and roasted electrolytic manganese slag according to an embodiment of the present invention is shown;
[0036] Figure 6 A schematic diagram of a compressive strength test process of a roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present invention adopts roasting electrolytic manganese slag, which has been desulfurized and fixed with ammonia during the roasting process, and the main production line has adopted cadmium removal treatment. Therefore, during the use process, only the Mn in the roasting electrolytic manganese slag needs to be considered. 2+ Ions, water-soluble salts, and pH issues.
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0040] The present embodiment provides a roadbed water-stabilizing layer material based on modified calcined electrolytic manganese manganese slag, including raw materials mixed in the following mass proportions: 3.0%-4.5% cement, 40%-60% coarse aggregate, 14%-27% calcined electrolytic manganese manganese slag, 1.12%-2.7% curing agent, 0.4%-0.75% stabilizer, 0.4%-0.75% activator and 1.93%-3.73% water.
[0041] This embodiment uses ordinary Portland cement, graded crushed stone, roasted electrolytic manganese manganese slag, quicklime, calcium-based bentonite, instant sodium silicate or water glass as the base material. Its essence is to use roasted electrolytic manganese manganese slag to replace part of the cement admixture and completely replace the fine aggregate component of the traditional water-stabilized layer, and use quicklime as a curing agent, calcium-based bentonite as a stabilizer, and instant sodium silicate or water glass as an activator to accelerate its gelation speed and curing efficiency. Only one hopper of the mixing station needs to be modified to realize the implementation method of the present invention. This embodiment is low in cost, easy to construct, and has been verified by indoor tests and field tests. The results are reliable, and it solves the problem of electrolytic manganese waste slag treatment for manganese mining enterprises and electrolytic manganese industry.
[0042] The new type of road water-stabilizing layer material made of roasted electrolytic manganese manganese slag in this embodiment uses ordinary Portland cement, graded crushed stone, roasted electrolytic manganese manganese slag, quicklime, calcium-based bentonite, instant sodium silicate or water glass as a base material. Its essence is to use roasted electrolytic manganese manganese slag to replace part of the cement addition and completely replace the fine aggregate component of the traditional water-stabilizing layer (accounting for 40%), and quicklime is used as a curing agent, calcium-based bentonite is used as a stabilizer, and instant sodium silicate or water glass is used as an activator, which can solidify the heavy metal ions and water-soluble salts of the roasted electrolytic manganese manganese slag. According to the appropriate proportion added in this embodiment, at the optimal moisture content, the activity of the roasted electrolytic manganese manganese slag as a cementitious material can be stimulated to form a water-stabilizing layer material, which is not easy to pollute the environment.
[0043] Preferably, in some embodiments, the mass ratios of ordinary Portland cement, graded crushed stone, calcined electrolytic manganese slag, quicklime, calcium-based bentonite, instant sodium silicate or water glass, and water are: 4%, 50%, 25%, 2%, 0.5%, 0.5%, and 3.45%, respectively.
[0044] Furthermore, in this embodiment, cement includes ordinary silicate cement solution, and its components include calcium silicate, calcium aluminate, calcium aluminoferrite, calcium sulfate and alkali. Cement mainly contains four materials, SiO2 (silicon dioxide), Al2O3 (aluminum oxide), Fe2O3 (ferric oxide), and CaO (calcium oxide), accounting for more than 95%. In this embodiment, cement is the main cementitious material of the water-stable layer, and the water-stable layer of the primary road generally accounts for 5.0% to 5.5%. In view of the fact that electrolytic manganese manganese slag can be used as a cementitious material, this embodiment reduces the cement dosage ratio and adopts a proportion of 3.0% to 4.5%, preferably 4.0% to 4.5%. After hydration, the components form the following ionic solution: calcium silicate (Ca2 + OH - ), calcium aluminate (Ca2 + 、Al(OH) 4- )Calcium aluminoferrate (Ca2 + 、Fe(OH) 4- ), calcium sulfate (Ca2+ 、SO4 2- ), alkali (K + 、Na + 、SO4 2- ). Specifically, the chemical reaction is as follows: (3CaO·SiO2)+6H2O→3CaO·2SiO2·3H2O+3Ca(OH)2;
[0045] 2(2CaO·SiO2)+4H2O→3CaO·2SiO2·3H2O+Ca(OH)2;
[0046] 3CaO·A12O3+6H2O→3CaO·A12O3·6H2O.
[0047] Furthermore, in the present embodiment, the fine aggregate includes roasted electrolytic manganese manganese slag, and the roasted electrolytic manganese manganese slag includes the following raw materials in proportion by mass: 31.80% silicon dioxide, 9.26% aluminum oxide, 5.54% iron oxide, 18.02% calcium oxide, 1.12% magnesium oxide, 13.49% manganese oxide and 12.87% sintering loss weight. Specifically, the four materials SiO2 (silicon dioxide), Al2O3 (aluminum oxide), Fe2O3 (ferric oxide) and CaO (calcium oxide) of the roasted electrolytic manganese manganese slag account for 70.16%. Therefore, the roasted electrolytic manganese manganese slag has certain cementitious material properties, but its manganese ion and water-soluble salt content are relatively high, and under the pH4.5 acid rain condition, the precipitated lead ion is slightly higher. Therefore, the present embodiment uses roasted electrolytic manganese manganese slag to replace part of the cement and completely replace part of the 40% fine aggregate of the traditional primary road water-stabilizing layer. The main components of the roasted electrolytic manganese slag in this embodiment are shown in Table 1. The results of element detection of the roasted electrolytic manganese slag are shown in Table 2. The roasted electrolytic manganese slag obtained in this embodiment is as follows: Figure 1 shown.
[0048] Table 1 Roasted electrolytic manganese slag as the main component of cementitious material
[0049] Ingredient name Quality Ratio Loss (sintering weight loss) 12.87 <![CDATA[SiO2 (Silicon Dioxide)]]> 31.80 <![CDATA[Al2O3 (Aluminum Oxide)]]> 9.26 <![CDATA[Fe2O3 (Iron(III) oxide)]]> 5.54 CaO (Calcium Oxide) 18.02 MgO(Magnesium Oxide) 1.12 MnO(Manganese Oxide) 13.49 Total content 92.10
[0050] Table 2 Element detection results of roasted electrolytic manganese slag
[0051]
[0052]
[0053] Furthermore, in this embodiment, the solidifying agent includes quicklime; the quicklime is mixed with the roasted electrolytic manganese slag to form a solidified precipitate, and the roasted electrolytic manganese slag contains a large amount of soluble manganese sulfate salts and heavy metals such as cadmium, chromium, and arsenic in the form of ions in a water-soluble state. Using the chemical precipitation method, the quicklime is converted into slaked lime in water, wherein the water-soluble sulfate of the roasted electrolytic manganese slag combines with calcium ions to react chemically to produce insoluble salts, forming calcium salt precipitation, and on the other hand, the hydroxide ions (OH - ) can react with many heavy metal ions (copper ions Cu 2+ 、Lead ion Pb 2+ 、Cd 2 + 、Zn ion Zn 2+ etc.) to form insoluble hydroxide precipitates, thereby reducing the concentration of soluble salts in the system and avoiding secondary pollution.
[0054] The specific reaction process is:
[0055] CaO+H2O=Ca(OH)2;
[0056] Mn 2+ +Ca(OH)2=Mn(OH)2↓+Ca 2+ ;
[0057] Ca(OH)2+Cd 2+ =Ca 2+ +Cd(OH)2;
[0058] Ca(OH)2+2As=Ca(AsO2)2+2H2O;
[0059] Ca(OH)2+CrO4 2- =CaCrO4↓+2OH - ;
[0060] Cu 2+ +2OH - =Cu(OH)2↓;
[0061] Pb 2+ +2OH - =Pb(OH)2↓;
[0062] Zn 2+ +2OH - =Zn(OH)2↓;
[0063] Hg 2+ +2OH - =HgO↓+H2O.
[0064] Indoor tests have verified that the greater the amount of calcium oxide added, the greater the calcium ion concentration, the greater the binding rate of soluble salts and heavy metals such as cadmium, chromium, and arsenic with calcium, and the higher the removal rate. However, excessive addition of calcium oxide will cause the pH of the leachate to be too high, which not only increases the economic cost, but also when used in the field, the excessively high pH of the effluent will affect the surrounding surface and groundwater environment, causing soil compaction. In order to determine the optimal amount of calcium oxide added, the experiment shows that when the ratio of quicklime to the mass of roasted electrolytic manganese manganese slag reaches 8% to 10%, its solidification and economic effects are optimal. This embodiment uses quicklime alone as a solidifying agent to solidify the roasted electrolytic manganese manganese slag. According to "HJ 557-2010 Solid Waste Leaching Toxicity Leaching Method-Horizontal Oscillation Method", the solidified roasted manganese slag is subjected to a leaching experiment. The specific solidification treatment results are shown in Table 3:
[0065] Table 3 Quicklime curing treatment effect
[0066]
[0067]
[0068] Therefore, when the quicklime mass ratio exceeds 8%, the quicklime to Mn 2+ The removal rates all reached over 98.5%, and the solidification rate of water-soluble salts increased with the increase of added amount.
[0069] In addition, high specific surface area calcium hydroxide is more capable of adsorbing heavy metal ions (copper ions Cu 2+ 、Lead ion Pb 2+ 、Cd 2+ 、Zn ion Zn 2+ wait).
[0070] Furthermore, in the present embodiment, the stabilizer includes calcium-based bentonite; the calcium-based bentonite adsorbs heavy metals in the roasted electrolytic manganese slag through the montmorillonite structure to prepare a cement stabilization layer. Specifically, in the present embodiment, calcium-based bentonite is a clay mineral rich in montmorillonite, which has a high water absorption and swelling capacity and cation exchange capacity. The properties of bentonite depend on the unique structure of montmorillonite. The heterovalent isomorphic substitution within the montmorillonite lattice is its most basic and important structural characteristic. Montmorillonite is a hydrated layered silicate mineral, and its basic structure consists of two layers of silicate sheets sandwiched by a layer of aluminum octahedron sheets. The general formula can be expressed as Na 0.33 [(Si4O 10 )2(OH)2].nH2O (where n is an arbitrary number). The main functional properties of bentonite come from the sodium (Na + ) or calcium (Ca 2+ ) and other exchangeable cations, such as Figure 2As mentioned above, manganese slag mainly contains MnO, Fe, CaO, SiO2 and other components, among which divalent manganese ions (Mn 2+ ) and ferric ions (Fe 3+ ) can exchange with bentonite under certain conditions, displacing the sodium ions between bentonite layers to generate new composite materials. The basic form of this reaction can be abstractly expressed as follows:
[0071] Na x [(Si4O 10 )2(OH)2].nH2O+yMn 2+ / Fe 3+ →[Mn / Fe] x [(Si4O 10 )2(OH)2]
[0072] Among them, y represents the Mn actually involved in the exchange reaction 2+ / Fe 3+ The molar number of x represents the number of sodium ions that can be replaced theoretically, and this value depends on the specific type and initial state of bentonite.
[0073] At the same time, there is a certain amount of Si in the silicon-oxygen tetrahedral sheet 4+ By Al 3+ This unequal substitution of similar substances makes the crystal layer produce a permanent negative charge. The negative charge of the crystal layer is mainly due to the electrostatic attraction of K + 、Na + , Ca 2+ The interlayer cations are balanced, and these interlayer cations are exchangeable. In addition, the edges of montmorillonite crystals are broken, and the end faces are negatively charged when pH>7, and a small amount of cations can also be adsorbed. It is precisely because of these characteristics of montmorillonite minerals that the manganese slag used in this embodiment has a pH greater than 9 to meet its adsorption conditions, so bentonite can adsorb some heavy metal cations that are not completely treated in the manganese slag under this condition, so that the manganese slag used to prepare the cement stabilization layer can meet the national standard requirements for slag treatment and utilization.
[0074] The interaction between bentonite and manganese slag is not limited to simple ion exchange, but may also be accompanied by other catalytic and solidification effects.
[0075] Furthermore, in the present embodiment, the activator includes instant sodium silicate or water glass. The instant sodium silicate can be used to make a 40°Bé water glass solution, or the 40°Bé water glass solution can be directly used. After the activator is added, the pH value of the calcined electrolytic manganese slag in the present embodiment under water-soluble conditions is 9.26-9.85. The main function of the activator is, on the one hand, to lower its pH value. On the other hand, according to indoor test reactions, the gelling time of different proportions of spherical and powdered forms is quite different. After water glass is mixed with the calcined electrolytic manganese slag, its coagulation is promoted by hydration reaction and pore filling. The coagulation effects caused by different water glass addition amounts are shown in Table 4, and the obtained gelling time is sampled as shown in Table 4. Figure 3 As shown, the obtained gelation time statistics are as follows Figure 4 shown.
[0076] Table 4 Coagulation effect of roasted electrolytic manganese slag under different water glass addition amounts
[0077]
[0078]
[0079] As a new type of active cementitious material, the coagulation and hardening reaction of electrolytic manganese slag is as follows:
[0080] 3CaO·SiO2+nH2O=2CaO·SiO2·(n-1)H2O+Ca(OH)2
[0081] The molecular structure of water glass in water is composed of silicate anions and cations such as sodium ions or potassium ions. These components combine with calcium ions in cement to form compounds such as CaSiO3 and Ca2SiO4, thereby accelerating the hardening process of cement. The reaction is as follows:
[0082] Ca(OH)2+NaO·nSiO2+mH2O→Ca·nSiO2·mH2O+NaOH
[0083] Adding water glass can also improve strength and durability: the high alkalinity of water glass can activate the activity of the calcined electrolytic manganese slag and reduce its solubility. And because of the high density and large molecules of water glass, it can form a network structure with the electrolytic manganese slag. The filling of large molecules makes the pores of the network structure denser, thereby improving its strength and durability as a new type of active cementitious material.
[0084] In addition, the impermeability and corrosion resistance are enhanced: the addition of water glass increases the density of the electrolytic manganese slag material, fills its pores, reduces the penetration of moisture and corrosive materials, and thus improves its impermeability and chemical stability.
[0085] In this embodiment, the indoor test results show that 1m 3The water addition ratio using 0.6% 40°Bé water glass solution can play a more economical and effective role.
[0086] Furthermore, in this embodiment, the coarse aggregate includes a graded crushed stone layer; the percentage of the first-level road particle size of the graded crushed stone layer is as follows: 4.75mm~9.5m particle size accounts for 10%, 9.5mm~19m particle size accounts for 35%, and 19mm~26.5m particle size accounts for 15%. Since the roasted electrolytic manganese manganese slag can be embedded with the coarse aggregate to form a dense graded cement stabilization layer, it has the characteristics of high density and high strength, and has good crack resistance and mechanical properties.
[0087] Finally, the material of this embodiment can undergo hydration reaction because the roasted electrolytic manganese slag has the characteristics of cementitious materials, but its effect cannot reach the performance of cement materials. According to indoor tests, its performance is between lime soil and cement. Therefore, it is necessary to accurately determine its optimal moisture content to best stimulate its cementitious activity. The material of this embodiment is obtained by determining the optimal water content of 13% of water added to the water-stabilizing layer and mixing it.
[0088] The present embodiment also provides a method for preparing a roadbed water-stabilizing layer material based on modified calcined electrolytic manganese manganese slag, comprising the following steps: mixing a curing agent and calcined electrolytic manganese manganese slag in a mass ratio of 8% to obtain a mixture; using instant sodium silicate to prepare or directly using 40°Bé water glass solution as an activator; adding 0.5% by mass of the activator, 0.5% by mass of the stabilizer, 4.0% by mass of the cement, and 50% by mass of the coarse aggregate to a 27% by mass mixture, and then adding 3.45% by mass of water to mix to obtain the roadbed water-stabilizing layer material.
[0089] This embodiment also provides an application of a roadbed water-stabilizing layer material based on modified calcined electrolytic manganese slag. Specifically, the roadbed water-stabilizing layer material is evenly laid on the road, wherein the loose laying thickness is 20-25cm, the compacted thickness is 15-20cm, and a 22t vibrating steel wheel roller roller is used to roll back and forth 4 times, which can meet the requirements of the first-class road for roadbed materials and mechanical properties.
[0090] The test experiment is as follows:
[0091] In order to further study the water-stabilized layer formed by ordinary Portland cement, graded crushed stone, roasted electrolytic manganese slag, quicklime, calcium-based bentonite, quick-dissolving sodium silicate or water glass, and water, this embodiment carried out unconfined compressive strength test research under different proportions, and the obtained samples were as follows Figure 5 As shown, the specific compressive strength test is as follows Figure 6 shown.
[0092] The different proportions and results of this embodiment are shown in Table 5-Table 9:
[0093] Table 5 The first group of test proportions and test results
[0094]
[0095] Table 6 The second group of test proportions and test results
[0096]
[0097]
[0098] Table 7 The third group of test proportions and test results
[0099]
[0100] Table 8 The fourth group of test proportions and test results
[0101]
[0102] Table 9 The fifth group of test proportions and test results
[0103]
[0104]
[0105] After the material of this embodiment is prepared, the compaction results obtained under its application are shown in Table 10:
[0106] Table 10 Compactness results of water-stabilizing layer materials prepared by electrolytic manganese slag
[0107] 22t steel wheel roller rolling times Compactness(%) Specifications and design requirements (%) 2 86.3~87.6 95 3 88.2~90.2 95 4 96.7~96.7 95
[0108] The test results show that, as a road water-stabilizing layer material, after adopting the ratio of the present invention, a 22t steel wheel drum roller is used to roll it 4 times, and the compaction degree is 96.793%, which meets the requirements of the specifications and designs for the compaction degree of the first-class road water-stabilizing layer of 93%, indicating its feasibility as a water-stabilizing layer material.
[0109] It should be noted that, for the above-mentioned method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the described order of actions, because according to the present invention, certain steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all optional embodiments, and the actions and modules involved are not necessarily required by the present invention.
[0110] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps described in the present invention can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solution disclosed in the present invention can be achieved, and this document does not limit this.
[0111] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag, characterized in that: The invention comprises raw materials in the following mass proportions: 3.0%-4.5% of cement, 40%-60% of coarse aggregate, 14%-27% of roasted electrolytic manganese slag, 1.12%-2.7% of curing agent, 0.4%-0.75% of stabilizer, 0.4%-0.7% of activator and 1.93%-3.73% of water.
2. The roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to claim 1, characterized in that: The cement comprises ordinary Portland cement, and the components of ordinary Portland cement include calcium silicate, calcium aluminate, calcium aluminoferrite, calcium sulfate and alkali.
3. The roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to claim 1, characterized in that: The roasted electrolytic manganese slag comprises raw materials in the following mass proportions: 31.80% silicon dioxide, 9.26% aluminum oxide, 5.54% iron oxide, 18.02% calcium oxide, 1.12% magnesium oxide and 13.49% manganese oxide.
4. The roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to claim 3, characterized in that: The solidifying agent comprises quicklime; the quicklime is mixed with the calcined electrolytic manganese slag to form a solidified precipitate; the mass ratio of the quicklime to the calcined electrolytic manganese slag is 8% to 10%.
5. The roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to claim 3, characterized in that: The stabilizer includes calcium-based bentonite or clay; the calcium-based bentonite adsorbs heavy metals in the roasted electrolytic manganese slag through the montmorillonite structure to prepare a cement stabilization layer.
6. The roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to claim 3, characterized in that: The activator includes instant sodium silicate or water glass, wherein the concentration of the water glass solution is 40° Bé; The instant sodium silicate or water glass is mixed with the cement and the calcined electrolytic manganese slag respectively, the cement is hardened and the electrolytic manganese slag network structure is prepared.
7. The roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to claim 3, characterized in that: The coarse aggregate comprises a graded crushed stone layer; The first-level road particle sizes of the graded crushed stone layer include: the mass ratio of the particle size of 4.75mm-9.5m is 10%, the mass ratio of the particle size of 9.5mm-19m is 35%, and the mass ratio of the particle size of 19mm-26.5m is 15%.
8. The roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to claim 1, characterized in that: The cement is ordinary Portland cement, the coarse aggregate is graded crushed stone, the curing agent is quicklime, the stabilizer is calcium-based bentonite, and the activator is quick-dissolving sodium silicate or water glass; The mass ratios of ordinary Portland cement, graded crushed stone, roasted electrolytic manganese slag, quicklime, calcium-based bentonite, instant sodium silicate or water glass, and water are 4%, 50%, 25%, 2%, 0.5%, 0.5%, and 3.45%, respectively.
9. The method for preparing a roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mixing a curing agent and a calcined electrolytic manganese slag in a mass ratio of 8% to obtain a mixture; Use instant sodium silicate or directly use 40°Bé water glass solution as the activator; 0.5% by mass of an activator, 0.5% by mass of a stabilizer, 4.0% by mass of cement, and 50% by mass of coarse aggregate are added to a 27% by mass mixture, and then 3.45% by mass of water is added and mixed to obtain the roadbed water-stabilizing layer material.
10. The use of the roadbed water-stabilizing layer material based on modified roasted electrolytic manganese slag according to any one of claims 1 to 8, characterized in that: The roadbed water-stabilizing layer material is evenly laid on the road, wherein the loose laying thickness is 20-25 cm, the compacted thickness is 15-20 cm, and a 22t vibrating steel wheel roller roller is used for rolling.
Citation Information
Patent Citations
Method for preparing construction material by utilizing electrolytic manganese slag
CN101570037B
Method using electrolytic manganese slag to manufacture active mixed material
CN105645793A
Method for preparing unfired concrete by adopting electrolytic manganese residues
CN109626885A
Electrolytic manganese slag containing road anti-cracking cement stabilized macadam material, and preparation method thereof
CN110423085A
Electrolytic manganese residue low-carbon roadbed material and preparation method thereof
CN114671640A
Cited By
Formula, preparation method and application of cement manganese slag stabilized macadam base mixture
CN121627361A